Level of uncertainty in adults with rheumatic diseases in a Chiclayo hospital, 2018 - Inoñan-Damian, María Del Rosario (2020)
Objetive. To determine the level of uncertainty according to the framework of stimuli, cognitive capacity and providers or sources of the structure, in adults with rheumatic diseases that are treated in an Chiclayo hospital, 2018. Material and methods: this study was descriptive, cross-sectional, had as a population 117 adults with diseases rheumatic, the sample was census and the sampling was not probabilistic. The Mishel Uncertainty Scale with reliability of Cronbach's alpha of 0.81 was used as an instrument. Results: the majority of adults with rheumatic diseases (79.49%) presented a level of regular uncertainty. The mean uncertainty level was 79.68 ± 9.39. The minimum score obtained was 59 and the maximum score was 111. Conclusion: Adults with rheumatic diseases presented a level of regular uncertainty, evidencing within the framework dimension of stimuli specifically, pattern of symptoms, familiarity of the event and congruence of the event. Likewise, in the cognitive capacity dimension and structure sources, it was obtained that adults considered that treatment and care were difficult to comply with; and the health personnel explained how to treat their disease, however, the information they provided was complex and they did not know how to distinguish the most important one.